Low reflecting hierarchically textured silicon by silver assisted chemical etching for potential solar cell application. (2018) - Singh, Prashant; Srivastava, Sanjay K.; Prajapati, Vijay; Sivaiah, B.; Rauthan, C.M.S.; Singh, P.K.
Abstract: Present study reports fabrication of silicon nanowires over micro-textured Si substrates. Silver assisted electroless chemical etching route has been adopted for fabrication of the nanowires. Influence of HF concentration on the formation kinetics has been investigated by using scanning electron microscopy. The hierarchical binary structures have been able to reduce solar weighted reflectance (SWR) to <3% in broad spectral range (300-1100 nm), from 38% SWR of the polished silicon without any additional coating. Such reduction in reflectivity is obtained for <1 µm nanowires length. It is observed that at relatively lower concentration of HF the nanowires are preferably formed only in <100> direction. However, with increase in the concentration, etching in both <100> and non-<100> directions such as <111> also occurs on the micro-pyramids of similar dimensions and results in the binary structures with slanted silicon nanowires on 3-dimansional micro-pyramids.